ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI KINERJA REKSA DANA SAHAM DI PASAR MODAL - Hasanah, Uswatun; Wulandari, Nurdea; Misra, Isra (Opportunity Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The results of the analysis found three main categories of variables that affect the performance of stock mutual funds: macroeconomic variables (inflation, interest rates, and exchange rates); mutual fund characteristics (size, age, and operational costs); and the ability of investment managers (the ability to choose securities and the ability to determine market time). While the influence of interest rates and exchange rates varies, the findings show that inflation generally has a negative impact on the performance ofstockmutual funds. The age ofmutualfunds usually has a positive impact on performance. This study shows that a holistic approach to assessing stock mutual funds is very important for investors; that investment managers should have a better ability to choose securities; and that regulators should make policies that increase the transparency and effectiveness of the mutual fund industry. This research increases our understanding ofthe dynamics ofstock mutual fund performance and shows areas that require further research in the context of the ever-changing capital market